Analisis Sikap dan Perilaku Konsumen Terhadap Produk Handphone Blackberry - Prasetyoning Tyas, Ari Anggarani Winadi (Lembaga Penerbitan Unversitas Esa Unggul, 2013)
AbstractThe proliferation of mobile Hand phone number of the company's products perform various USAA to create a product that excels in marketing activities, companies need a strategy to influence the market by looking for business opportunities in the form of in the form of products and services. Given the scale of the needs of the community and realize the importance of Mobile, recently appeared a brand called Blackberry Mobile Phones. BlackBerry is a mobile device that has the ability to push e-mail, telephone, SMS, Browsing the Internet, and various other wireless capabilities. The use of this advanced gadget so phenomenal in recent years, until it becomes a necessity for fashion. Respondents' attitudes toward Mobile Blackberry is positive which means that the respondents liked the Blackberry Mobile products where the value is equal to 3,38 manner in which entry into the important category and consider Blackberry Mobile Promotion which includes promotional ads in various media and bundling with several mobile operators is the the most dominant influences consumers. Consumer behavior on Mobile Blackberry was 2.18, which means consumers still use Blackberry Mobile, Blackberry in making a purchase. Seller consumers follow the advice. Compared advice Friend and Promotion.Keywords : attitude, behavior, product